Characteristics of ER, PR, HER2 and Ki67 Expression in Invasive Breast Cancer Patients at RSUP Dr. Wahidin Sudirohusodo, Makassar 2021-2023 - Rahmawani, Surya; Nelwan, Berti J; Miskad, Upik Anderiani; Cangara, Muhammad Husni; Sungowati, Ni Ketut; Yamin, Amalia; Aslam, Muhammad; Mardiati, Mardiati (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Invasive breast carcinoma is the most common type of breast cancer among women globally, with high mortality. In Indonesia, it ranks first based on Globocan 2020 data. Objective: To determine the expression of prognostic and predictive markers—Estrogen Receptor (ER), Progesterone Receptor (PR), HER2, and Ki67—in breast cancer cases at RSUP Wahidin Sudirohusodo. Methods: A descriptive study was conducted on 71 samples from 2021–2023. Data on age, histopathologic grade, and marker expression (HER2, ER, PR, Ki67) were analyzed. Samples were stained and examined microscopically. Chi-square tests were performed using SPSS version 27. Results: Among the 71 samples, 47.89% were from patients aged < 50 years and 52.11% from those >/ 50. Grade 2 was most common (59.15%). HER2 expression was negative in 59.15% of samples, ER positive in 83.10%, PR positive in 67.61%, and Ki67 expression was low in 52.11%. Conclusion: Most cases showed negative HER2 and positive ER/PR expression with low Ki67, indicating the relevance of hormonal receptors and proliferation rate as prognostic indicators. These markers are crucial for prognosis and treatment planning in breast carcinoma.